Diagnostic Accuracy of Kramer Visual Assessment of Jaundice in Term Neonates Taking Total Serum Bilirubin Levels as the Gold Standard - Mumtaz, Shaista; Shafiq, Muhammad Faisal; Khan, Kenan Anwar; Hussain, Murtaza; Rahman, Asbah; Shafiq, Sania (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine the Diagnostic accuracy of Kramer’s visual assessment of jaundice in term neonates by taking total serum bilirubin levels as a gold standard. Study Design: Cross-sectional study. Place and Duration of Study: Neonatology Department, Pak Emirates Military Hospital, Rawalpindi Pakistan, Mar to Sep 2019. Methodology: The study was based on examining and investigating 300 neonates. Kramer scale was used to examine jaundice in all neonates, and results were compared to total serum bilirubin levels. Results: A total of 300 patients were included in this study. The mean bilirubin level was 229.1±74.5mol/L. The sensitivity and specificity of visual assessment of jaundice using the Kramer visual scale were 83.84% and 73.53%, respectively, for neonates who were not jaundiced below the abdomen and thighs included in Kramer zones 1 to 3. Conclusion: Kramer visual assessment can be used as a noninvasive screening method in neonates jaundiced up to the abdomen and thighs, which is included in Kramer zones 1 to 3 but for markedly jaundiced neonates Kramer scale is not a reliable noninvasive method of bilirubin estimation.